READINESS FOR SELF-DEVELOPMENT OF FUTURE TEACHERS OF HUMANITARIAN SPECIALTIES - Horianska, Anzhelika; Pisotskyi, Vadym (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article presents the results of theoretical analysis of the phenomenon of "readiness for self-development" and empirical study of its psychological features in future teachers. The purpose of the study is to theoretically analyze the specifics of future teachers’ readiness for self-development and empirically identify its psychological characteristics. A substantive analysis of the concept of "readiness for self-development" in future teachers is carried out. It is stated that this phenomenon is considered as a psychological formation in the structure of self-consciousness, which accumulates the possibilities of human self-movement, develops the ability to positively perceive the world and consciously form important traits, promoting personal and professional growth, achieving self-improvement and self-realization; as a complex phenomenon, the structure of which is formed by goals and motives, assessment of one’s own abilities, experience, ability to self-development and self-education, self-management skills, professional orientation, aptitude for the profession, self-regulation and self-management, and strong-willed traits. The empirical study was conducted in February-March 2023. Using the following methods: The Readiness for Self-Development test and the SAMOAL questionnaire, the results were obtained according to 14 criteria that indicate signs of readiness for self-development of future teachers. Results. The following were found: the prevalence of the need for readiness for self-knowledge over the need for self-improvement; positive motivational attitude of self-development; tendency to immerse oneself in the problems of the past or project one’s future; contradictory trends in self-esteem mechanisms; tendency to effectively disclose oneself in relationships with colleagues; desire for originality in one’s own life, desire for integrity. It is concluded that readiness for self-development is a complex phenomenon that plays an important role in the professional development of future teachers; students have psychological characteristics of readiness for self-development, which are manifested in attitudes and behavior; students try to reveal themselves in relationships, tune in to fruitful personal communication, strive to avoid manipulation of people, show interest in new experiences, strive for originality, integrity of their personality